Answer:
1. -5 and -8
2. -7 and -4
3. -15 and -1
4. 7 and -2
5. -5 and 1
6. 2 and -5
7. -8 and 9
8. 5 and -4
Step-by-step explanation:
Answer:
(x+4)....................
Answer:
![\sqrt[4]{x^{7} }](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7Bx%5E%7B7%7D%20%7D)
Step-by-step explanation:
this is the same concept basically as simplifying
into
. You can see that the denominator is in front of the radical and that any numbers in the numerator are the power of the number underneath.
The value of the given expression (3m - n)² + 4m when m = 63 and n = 45 is equal to 20,916.
<h3>What is an expression?</h3>
An expression can be defined as a mathematical equation which is used to show the relationship existing between two or more variables and numerical quantities.
<u>Given the following variables:</u>
Substituting the given variables into the given expression, we have;
Expression = (3m - n)² + 4m.
Expression = (3(63) - 45)² + 4(45).
Expression = (189 - 45)² + 180
Expression = 144² + 180
Expression = 20,736 + 180
Expression = 20,916.
Read more on expressions here: brainly.com/question/28260012
#SPJ1
Complete Question:
Evaluate the expression when m = 63 and n = 45. (3m - n)² + 4m.
Get the x terms by themselves on one side and a constant on the other side of the equal sign...
4x^2-8x=1 make the leading coefficient equal to one...
x^2-2x=1/4 now halve the linear coefficient, -2 in this case, square it, and add that value to both sides of the equation...-2/2=-1, -1^2=1 so
x^2-2x+1=1+1/4
x^2-2x+1=5/4 now the left side is a perfect square...
(x-1)^2=5/4 take the square root of both sides...
x-1=±√(5/4) add 1 to both sides
x=1±√(5/4)